Enzymes required for maltodextrin catabolism in Enterococcus faecalis exhibit novel activities - Joyet, Philippe (2017)
Maltose and maltodextrins are formed during the degradation of starch or glycogen. Maltodextrins are composed of a mixture of maltooligosaccharides formed by α-1,4- but also some α-1,6-linked glucosyl residues. The α-1,6-linked glucosyl residues are derived from branching points in the polysaccharides. In Enterococcus faecalis, maltotriose is mainly transported and phosphorylated by a phosphoenolpyruvate:carbohydrate phosphotransferase system. The formed maltotriose-6α-phosphate is intracellularly dephosphorylated by a specific phosphatase, MapP. In contrast, maltotetraose and longer maltooligosaccharides up to maltoheptaose are taken up without phosphorylation via the ATP binding cassette transporter MdxEFG-MsmX. We show that the maltose-producing maltodextrin hydrolase MmdH (GenBank accession no. EFT41964) in strain JH2-2 catalyzes the first catabolic step of α-1,4-linked maltooligosaccharides. The purified enzyme converts even-numbered α-1,4-linked maltooligosaccharides (maltotetraose, etc.) into maltose and odd-numbered (maltotriose, etc.) into maltose and glucose. Inactivation of mmdH therefore prevents the growth of E. faecalis on maltooligosaccharides ranging from maltotriose to maltoheptaose. Surprisingly, MmdH also functions as a maltogenic α-1,6-glucosidase, because it converts the maltotriose isomer isopanose into maltose and glucose. In addition, E. faecalis contains a glucose-producing α-1,6- specific maltodextrin hydrolase (GenBank accession no. EFT41963, renamed GmdH). This enzyme converts panose, another maltotriose isomer, into glucose and maltose. A gmdH mutant had therefore lost the capacity to grow on panose. The genes mmdH and gmdH are organized in an operon together with GenBank accession no. EFT41962 (renamed mmgT). Purified MmgT transfers glucosyl residues from one α-1,4-linked maltooligosaccharide molecule to another. For example, it catalyzes the disproportionation of maltotriose by transferring a glucosyl residue to another maltotriose molecule, thereby forming maltotetraose and maltose together with a small amount of maltopentaose.